The Double-Mirror Gaze, Transcoded Testimony, and Disqualified Witnesses in the Talmud - Dickmann, Iddo (The journal of Jewish thought & philosophy, 2023)
I will argue that the underlying rationale for the talmudic list of trades disqualified from legal testimony is aesthetic. These trades involved professional mimicry, which as such incapacitated what R. Neis has termed “homovisuality” or self-referential witnessing in the Talmud. Reading talmudic laws of conjoined testimony and the induction of witnesses in light of Deleuze’s and Blanchot’s philosophy, I will argue that homovisuality entailed the witness’s reincarnation as the subject of the event, thus re-signifying rather than reporting the event. The judge, transformed into a witness, could capture the truth of the event at a glance, in a manner both prior to and irreducible to trial procedures.